Influenza pathogenesis and control - volume I - Oldstone, Michael B. A.; Compans, Richard W. (Current Topics in Microbiology and Immunology, 2014)
This two-volume work covers the molecular and cell biology, genetics and evolution of influenza viruses, the pathogenesis of infection, resultant host innate and adaptive immune response, prevention of infection through vaccination and approaches to the therapeutic control of infection.. Experts at the forefront of these areas provide critical assessments with regard to influenza virology, immunology, cell and molecular biology, and pathogenesis. Volume I provides overviews of the latest findings on molecular determinants of viral pathogenicity, virus entry and cell tropism, pandemic risk assessment, transmission and pathogenesis in animal species, viral evolution, ecology and antigenic variation, while Volume II focuses on the role of innate and adaptive immunity in pathogenesis, development of vaccines and antivirals.